Jika f(x) = x²- 2x² + 3x – 1 dan g(x) = x² + x – 2, maka f(x) + g(x) adalah ..

Posted on

A. x3 – x² – 4x + 3
B. x3 – x² + 4x 3
C. x3 +- x² – 4x – 3
D. x3 + x² + 4x + 3
E. x3 + x² – 4x – 3​

Jika f(x) = x²- 2x² + 3x – 1 dan g(x) = x² + x – 2, maka f(x) + g(x) adalah ..

Penjelasan dengan langkah-langkah:

f(x) = x^3 – 2x^2 + 3x – 1

g(x) = x^2 + x – 2

maka:

f(x) + g(x)

= x^3 – 2x^2 + 3x – 1 + (x^2 + x – 2)

= x^3 – 2x^2 + x^2 + 3x + x – 1 + (-2)

= x^3 – x^2 + 4x – 3

Jawaban : B

^ (pangkat)